Minority-carrier effects in poly-phenylenevinylene as studied by electrical characterization - Stallinga, Peter (2015)
Electrical measurements have been performed on poly[2-methoxy, 5 ethyl (2' hexyloxy) paraphenylenevinylene] in a pn junction with silicon. These included current-voltage measurements, capacitance-voltage measurements, capacitance-transient spectroscopy, and admittance spectroscopy. The measurements show evidence for large minority-carrier injection into the polymer possibly enabled by interface states for which evidence is also found. The shallow acceptor level depth (0.12 eV) and four deep trap level activation energies (0.30 and 1.0 eV majority-carrier type; 0.48 and 1.3 eV minority-carrier type) are found. Another trap that is visible at room temperature has point-defect nature. (C) 2001 American Institute of Physics.